User Feasibility Study on the Digitization of Jawi Imprints Collection - Wan Jumanatun Nailiah Wan Muh Syahrir; Sharifah Nur Amirah Sarif Abdullah (Journal of Computing Technologies and Creative Content, 2025)
Jawi literature is recognized as a Malay literary heritage, a rare and scarce collection that resulted in a call for preservation. One of the promising ways of preservation today is the technology of digitization. To date, studies have been published on the digitization of Jawi literature primarily concerning Malay Jawi manuscripts collection. Meanwhile, the Jawi imprints were discussed far less frequently. Thus, this study brings users to the forefront of the research in assessing their perceptions on digitization technology for Jawi imprints collection. This study employed a quantitative analysis and collected data from respondents through a questionnaire. The findings indicated that from users’ perception, the digitization technology is probable for Jawi imprints collection, based on the measurement of their awareness, acceptance, and readiness. Further, the voluntary answers from respondents when they were asked to appraise any opinion that they wanted to add regarding the digitization of Jawi imprints collection have ascertained the importance to fulfil this effort together with lengthy commentaries. This study has contributed significantly to understanding the current status of the usage of Jawi imprints collection as well as users’ perceptions towards the digitization for this collection